Human capital and career success: Evidence from linked employer-employee data - Anders Frederiksen; Takao Kato (Institute for the Study of Labor (IZA), 2011)
Denmark's registry data provide accurate and complete career history data along with detailed personal characteristics (e.g., education, gender, work experience, tenure and others) for the population of Danish workers longitudinally. By using such data from 1992 to 2002, we provide rigorous evidence for the first time for the population of workers in an entire economy (as opposed to case study evidence) on the effects of the nature and scope of human capital on career success (measured by appointments to top management). First, we confirm the beneficial effect of acquiring general human capital formally through schooling for career success, as well as the gender gap in career success rates. Second, broadening the scope of human capital by experiencing various occupations (becoming a generalist) is found to be advantageous for career success. Third, initial human capital earned through formal schooling and subsequent human capital obtained informally on the job are found to be complements in the production of career success. Fourth, though there is a large body of the literature on the relationship between firm-specific human capital and wages, the relative value of firm-specific human capital has been rarely studied in the context of career success. We find that it is more beneficial to broaden the breadth of human capital within the firm than without, pointing to the significance of firm-specific human capital for career success.
urn:nbn:de:101:1-201106202197
Keywords: J24; M5; 330; human capital; career development; occupations; internal promotion; external recruitment; top management